Student E-Learning Satisfaction During The Covid-19 Pandemic in Bali, Indonesia - Ni Kadek Suryani; Ida Ayu Putu Widani Sugianingrat (Jurnal Economia, 2021)
Abstract: The Covid-19 has led to comprehensive changes in the education sector. Physical distancing requirements have seen education programs in Denpasar city, Bali province, Indonesia move online. During the Covid-19 pandemic from February-May) 2020, this study was conducted to determine student e-learning satisfaction and e-learning system success. Student satisfaction was measured by e-learning attitude, e-learning quality, and e-learning flexibility. The research was conducted at two private universities in Bali, Indonesia and involved 257 respondents. Respondents were student actively engaged in e-learning during Covid-19. The results found a significant positive relationship between student e-learning attitude and e-learning quality on student e-learning satisfaction, and also student e-learning satisfaction on e-learning system success; however, the influence of e-Learning flexibility on student e-learning satisfaction was not significant. Universities can improve e-learning results by considering the technical limitation students face for e-learning and improving the flexibility of access to online teachers.Keywords: e-learning attitude, e-learning quality, e-learning  flexibility, student e learning satisfaction, e-learning system successKepuasan Siswa Mengikuti E-Learning Selama Pandemi Covid-19 di IndonesiaAbstrak:Terjadinya pandemi Covid-19 mengakibatkan berbagai perubahan terjadi di seluruh dunia, termasuk di sektor pendidikan. Penerapan jarak fisik menyebabkan program pembelajaran dilakukan secara online, termasuk pada program pendidikan di kota Denpasar, Provinsi Bali, Indonesia. Penelitian ini dilakukan selama pandemi Covid-19 (Feb-Mei) 2020, bertujuan untuk mengetahui kepuasan mahasiswa mengikuti program e-Learning dan keberhasilan program e-Learning selama pandemi Covid-19. Pengukuran kepuasan mahasiswa dilakukan melalui variabel sikap mahasiswa, kualitas e-learning, dan fleksibilitas e-learning. Lokasi penelitian dilakukan di dua Universitas swasta di Bali, Indonesia, dengan populasi 718 dan 257 sampel yang diambil menggunakan formula Slovin. Responden adalah mahasiswa aktif yang mengikuti e-learning selama Covid-19. Data dianalisis menggunakan program SmartPLS 3,0. Hasil menemukan bahwa tiga hipotesis diterima dan satu hipotesis ditolak dari empat hipotesis yang diusulkan. Universitas diharapkan untuk memperhatikan waktu dan tempat pelaksanaan yang nyaman bagi mahasiswa dalam mengikuti pembelajaran e-learning demi meningkatkan kepuasan mereka terhadap program e-learning.Kata kunci: sikap e-learning, kualitas e-learning, fleksibilitas e-learning, kepuasan e-learning siswa, keberhasilan sistem e-learning